Strategic analysis of the supply and the demand for organic foods in Spain - Robles R.; De la Puente I.; Morán J.; Juán A. (The market for organic products in the Mediterranean region, 2003)
Just as was experienced by the rest of Europe, Spanish organic agricultural output experienced a remarkable growth during the decade of the 90s. Nevertheless, this important advance contrasts with the data referring to internal consumption, with exports being the main destination for most of this food supply. At the beginning of the 21st Century, the continuity of this situation could mean an important restriction in the development of a sector that currently enjoys considerable administrative support, both at the Spanish and European level, and which has been consolidated as one of the most important instruments within the agrarian and rural development policies. This study aims to carry out a strategic analysis of the current situation in Spain with regard to the supply and demand for this kind of product. For this purpose, information from secondary or primary sources has been compiled in order to make a SWOT Analysis, which will enable the strengths, weaknesses, threats and opportunities arising from the supply and demand for this type of product to be identified and which could serve as a starting point for the devising of subsequent strategies to promote the development of the sector.
Intensive Course in: Marketing of Organic Products, 2002/05/20-31, Izmir (Turkey)